Predictors of postpartum depression among mothers in Wenzhou, China: A cross-sectional study - Yufan Huang; Punyarat Lapvongwatana; Tatirat Tachasuksri (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Postpartum depression (PPD) significantly impacts maternal well-being, infant development, and family functioning. Studies examining interrelationships among multiple predictors using theoretical frameworks in Chinese populations remain limited. Objective: To determine the prevalence of postpartum depression and examine the associations of biological, psychological, and social factors among postpartum women in Wenzhou, China. Methods: A predictive correlational cross-sectional study was conducted at a tertiary hospital in Wenzhou from November to December 2024. Using systematic random sampling, 166 postpartum women aged 20-44 years, within 4 weeks to 6 months postpartum, were recruited. Data were collected using validated instruments, including the Edinburgh Postnatal Depression Scale (EPDS), Rosenberg Self-Esteem Scale, Maternal Breastfeeding Evaluation Scale, Revised Dyadic Adjustment Scale, and Stryker Adjustment Checklist. Multiple regression and mediation analyses using the PROCESS macro with bootstrap resampling were performed to identify significant predictors and examine mediating pathways. Results: The prevalence of PPD (EPDS score ≥9) was 21.1%. Multiple regression analysis revealed that breastfeeding satisfaction (β = -0.419, p < 0.001) and fulfillment of infant gender expectations (β = -0.202, p = 0.006) were significant predictors, together accounting for 28.4% of the variance in PPD symptoms.Mediation analysis indicated that breastfeeding satisfaction partially mediated the relationship between infant gender expectations and PPD. Pregnancy complications, self-esteem, marital satisfaction, and mother-in-law relationships were not statistically significant predictors in the final model. Conclusion: Approximately one in five postpartum women in Wenzhou experienced clinically significant depressive symptoms. Fulfilled gender expectations were associated with lower PPD risk, partially mediated by higher breastfeeding satisfaction, supporting the Biopsychosocial Model. These findings highlight the need for routine PPD screening, satisfaction-focused breastfeeding support, culturally sensitive counseling regarding family gender expectations, and family-centered interventions in postpartum care.